Structural and optical properties of Zno nanostructures. - Pung, Swee-Yong (Asean Engineering Journal)
The structural and crystal quality of ZnO film, Au-catalyzed ZnO nanowires (NWs) and catalyst-free ZnO NWs were studied. ZnO film deposited at 145 degree celcius by atomic layer deposition (ALD) had a smooth surface (RMS roughness : 2.850 nm), high transmittance in the visible light region (89.9+6.7 percent) and good film resistivity (4.131x10-3 .cm). Thus, ZnO films with these attractive properties are suitable for transparent conducting oxide (TCO) applications. Both catalyst-free ZnO NWs and Au-catalyzed ZnO NWs were grown using chemical vapour deposition (CVD). Vertically aligned ZnO NWs (catalyst-free) could be synthesized using highly (002) oriented ZnO seed film pre-deposited on silicon substrate. The catalyst-free ZnO NWs exhibited the best crystal quality as it showed the largest percentage of Zn-O bonds in XPS analysis and highest UV/visible ration in PL measurement. However, randomly grown AU catalyzed ZnO NWs were synthesized on bare silicon substrate. The randomly grown NWs has been attributed to the large lattice mismatch between ZnO and silicon wafer. The growth of Au-catalyzed ZnO NWs was proposed to be governed by Vapour-Liquid Solid_Vapour Solid (VLS-VS) mechanism.